Almost periodic solutions of retarded SICNNs with functional response on piecewise constant argument. Issue 8 (November 2016) - Akhmet, Marat; Fen, Mehmet; Kirane, Mokhtar
Abstract We consider a new model for shunting inhibitory cellular neural networks, retarded functional differential equations with piecewise constant argument. The existence and exponential stability of almost periodic solutions are investigated. An illustrative example is provided.